The Green Paper on the EU asylum system: Necessary but not sufficient - Steffen Angenendt; Roderick Parkes (Stiftung Wissenschaft und Politik (SWP), 2007)
In its 2004 Hague Programme, the European Council prescribed the adoption of the "second phase" of the Common European Asylum System before the end of 2010. In the first phase, elaborated within the framework of the preceding Tampere Programme, minimum standards for refugee protection had been adopted; these were now to be improved. Seeking to foster the necessary debate and impetus, the European Commission presented a Green Paper on the subject in June 2007. The Paper certainly contains useful suggestions for future harmonisation, yet with its exclusive focus on asylum policy it may be found wanting. The supreme problem facing asylum policy-makers today - "mixed" immigration flows comprising both forced and economically-motivated migrants - cannot be tackled without at least a consideration of the extension of channels for economic immigration. Against this background, improving protection standards may require the further integration of asylum policy into the European Union's so-called Global Approach towards Migration
Keywords: 320